A Giant Duodenal Leiomyoma Showing Increased Uptake on 18F-Fluorodeoxyglucose Positron Emission Tomography - Keisuke Nonoyama; Hidehiko Kitagami; Akira Yasuda; Shiro Fujihata; Minoru Yamamoto; Yasunobu Shimizu; Moritsugu Tanaka (Case Reports in Surgery)
Background. Although 18F-fluorodeoxyglucose positron emission tomography (FDG-PET/CT) is now widely used in their differential diagnosis, it is sometimes difficult to distinguish between benign and malignant diseases. Case Presentation. A 44-year-old woman was found to have abnormalities on health screening. Magnetic resonance imaging for detailed examination showed an intra-abdominal tumor measuring 12 cm in the major axis near the cranial end of the uterus. Upper gastrointestinal tract endoscopy showed a tumor with an ulcer in the third part of the duodenum, involving half the circumference. Heterogeneous uptake was observed within the tumor on FDG-PET/CT. Based on these findings, the patient underwent surgery for suspected primary malignant lymphoma of the duodenum or gastrointestinal stromal tumor. Laparotomy revealed a 12 cm tumor in the third part of the duodenum. Partial duodenectomy and end-to-end duodenojejunostomy were performed. Pathological findings showed a solid tumor growing from the muscle layer of the duodenum to outside the serous membrane; based on immunostaining, it was diagnosed as a leiomyoma. Conclusions. Duodenal leiomyomas are originally benign; to date, there have been no reports of uptake in duodenal leiomyomas on FDG-PET/CT; therefore, our case is rare. Leiomyomas should be considered in the differential diagnosis of duodenal neoplastic diseases.